Retinal adaptation to dim light vision in spectacled caimans (Caiman crocodilus fuscus): Analysis of retinal ultrastructure. (August 2018) - Karl, Anett; Agte, Silke; Zayas-Santiago, Astrid; Makarov, Felix N.; Rivera, Yomarie; Benedikt, Jan; Francke, Mike; Reichenbach, Andreas; Skatchkov, Serguei N.; Bringmann, Andreas
Abstract: It has been shown that mammalian retinal glial (Müller) cells act as living optical fibers that guide the light through the retinal tissue to the photoreceptor cells (Agte et al., 2011; Franze et al., 2007). However, for nonmammalian species it is unclear whether Müller cells also improve the transretinal light transmission. Furthermore, for nonmammalian species there is a lack of ultrastructural data of the retinal cells, which, in general, delivers fundamental information of the retinal function, i.e. the vision of the species. A detailed study of the cellular ultrastructure provides a basic approach of the research. Thus, the aim of the present study was to investigate the retina of the spectacled caimans at electron and light microscopical levels to describe the structural features. For electron microscopy, we used a superfast microwave fixation procedure in order to achieve more precise ultrastructural information than common fixation techniques. As result, our detailed ultrastructural study of all retinal parts shows structural features which strongly indicate that the caiman retina is adapted to dim light and night vision. Various structural characteristics of Müller cells suppose that the Müller cell may increase the light intensity along the path of light through the neuroretina and, thus, increase the sensitivity of the scotopic vision of spectacled caimans. Müller cells traverse the whole thickness of the neuroretina and thus may guide the light from the inner retinal surface to the photoreceptor cell perikarya and the Müller cell microvilli between the photoreceptor segments. Thick Müller cell trunks/processes traverse the layers which contain light-scattering structures, i.e., nerve fibers and synapses. Large Müller cell somata run through the inner nuclear layer and contain flattened, elongated Müller cell nuclei which are arranged along the light path and, thus, may reduce the loss of the light intensity along the retinal light path. The oblique arrangement of many Müller cell trunks/processes in the inner plexiform layer and the large Müller cell somata in the inner nuclear layer may suggest that light guidance through Müller cells increases the visual sensitivity. Furthermore, an adaptation of the caiman retina to low light levels is strongly supported by detailed ultrastructural data of other retinal parts, e.g. by (i) the presence of a guanine-based retinal tapetum, (ii) the rod dominance of the retina, (iii) the presence of photoreceptor cell nuclei, which penetrate the outer limiting membrane, (iv) the relatively low densities of photoreceptor and neuronal cells which is compensated by (v) the presence of rods with long and thick outer segments, that may increase the probability of photon absorption. According to a cell number analysis, the central and temporal areas of the dorsal tapetal retina, which supports downward prey detection in darker water, are the sites of the highest diurnal contrast/color vision, i.e. cone vision and of the highest retinal light sensitivity, i.e. rod vision. Highlights: Retinal ultrastructure of the spectacled caiman reveals adaptions to dim light vision. Rod dominance and retinal tapetum suggest an increase in retinal light sensitivity. Single-rowed photoreceptor nuclei penetrate the outer limiting membrane. Radial Müller glial cells may improve light transmission through the neuroretina. Ellipsosomes in double cones may improve visual contrast under twilight conditions.